A Roman late-republican gladius from the River Ljubljanica (Slovenia) - Istenič, Janka (Arheološki vestnik, 2000)
A Roman sword in its scabbard was found in the River Ljubljanica about 4.5 km down-stream from Nauportus. On the front of the scabbard is a net-like fitment for which just a few analogies exist. Two extremely unusual fitments are apparent on the back of the scabbard: a thin flat rectangular fitment surmounted, in the middle, by a substantial protruding fitment with two holes. The length and proportions of the scabbard as well as its elongated point are indicative of a late-republican date. It may be seen as the typological predecessor of its closest parallel, that is, the sword in a scabbard from Magdalensberg, which was found in a layer dated to c. 30-20 B.C. The sword and scabbard from the Ljubljanica can be dated to about the beginning of the second decade of the first century B.C. The PIXE analyses showed that all the fitments on the scabbard were made of brass. A study of the beginnings of the use of brass has shown that Augustus’ monetary reform of 23 B.C. was not synchronous with the introduction of brass technology to Roman Italy, and that occurance of brass fitments on a scabbard dated to the beginning of the second half of the first century B.C. is not unexpected.